A technical comparison of three low earth orbit satellite constellation systems to provide global broadband. (June 2019) - del Portillo, Inigo; Cameron, Bruce G.; Crawley, Edward F.
Abstract: The idea of providing Internet access from space has made a strong comeback in recent years. After a relatively quiet period following the setbacks suffered by the projects proposed in the '90s, a new wave of proposals for large constellations of low Earth orbit (LEO) satellites to provide global broadband access emerged between 2014 and 2016. Compared to their predecessors, the main differences of these systems are: increased performance that results from the use of digital communication payloads, advanced modulation schemes, multi-beam antennas, and more sophisticated frequency reuse schemes, as well as the cost reductions from advanced manufacturing processes (such as assembly line, highly automated, and continuous testing) and reduced launch costs. This paper compares three such large LEO satellite constellations, namely SpaceX's 4425 satellites Ku-Ka-band system, OneWeb's 720 satellites Ku-Ka-band system, and Telesat's 117 satellites Ka-band system. First, we present the system architecture of each of the constellations (as described in their respective FCC filings as of September 2018), highlighting the similarities and differences amongst the three systems. Following that, we develop a statistical method to estimate the total system throughput (sellable capacity), considering both the orbital dynamics of the space-segment and the variability in performance induced by atmospheric conditions both for the user and feeder links. Given that the location and number of ground stations play a major role in determining the total system throughput, and since the characteristics of the ground segment are not described in the FCC applications, we then run an optimization procedure to minimize the total number of stations required to support the system throughput. Finally, we conclude by identifying some of the major technical challenges that the three systems will have to overcome before becoming operational. Highlights: Technical overview of the architecture of OneWeb, SpaceX and Telesat LEO constellations. Comparison in terms of satellites in LoS, frequency allocation, beam characteristics. Analysis of ground segment requirements and impact on system capacity. Statistical estimates of the total system throughput (sellable capacity) for each system.